An entropy-based approach to stock market volatility: evidence from the G7’s market indices - Bentes, S. R. (2017)
This paper examines the adequacy of entropy in assessing stock market volatility. To this end, we compare the traditional approach based on the standard deviation with the entropy method. In view of the fact that the Shannon entropy is only suitable for describing equilibrium systems we consider Renyi and Tsallis entropies, which are more appropriate to explain anomalous phenomena. We used a sample based on the daily returns of the G7's major stock market indices. The results show the limitations of the standard deviation-based approach in fully characterising volatility and highlight the potentialities of entropy as a measure of uncertainty.